La Estomatología ante el reto de la salud universal - Gispert Abreu, Estela de los Ángeles (Revista Cubana de Estomatología, 2018)
Stomatology is a Health Science that is projected obeying contextual, political, social and organizational issues of health services, although it is recognized that it can be more effective if it is directed towards population health and develops in the setting of the strategy of Primary Health Care.1-3 Due to their professional profile, stomatologists (or dentists), technologists and technicians must contribute to the care of population health, demonstrating leadership within the health team, for decision making and the formulation of healthy public policies that benefit the population’s oral health. at a local, national and global level. This makes knowledge and scientific updating essential not only in technical aspects but also in matters of public health, social sciences, behavioral sciences; as well as in bioethical principles and the right to health, so as to reinforce the commitment to social welfare.4-6 The actions for oral health care should be developed throughout the life cycle, adapt to different contexts and circumstances. To increase oral health levels, it is necessary to ensure that health professionals, the population and sectors of society assume a favorable behavior to their maintenance or recovery 1,7,8 and to employ more conservative technologies ─ in diagnosis, prevention and restoration─; together with the offer of quality services, accessible to the entire population, with projection and social impact. The stomatological profession, at a global level, continues to provide greater attention to the so-called "art" that reveres the aesthetics of restorative treatments and tends to reduce the patient to the structure to be treated in the clinic, decontextualizing it from its social environment.